HUBUNGAN HUKUM DAN PERTANGGUNGJAWABAN WAKIL PIALANG BERJANGKA DI BIDANG PERDAGANGAN BERJANGKA KOMODITI (Mimbar Keadilan, 2022)
A futures broker is a business entity that arranges commodity trading activities based on futures contracts, Islamic derivatives, and/or other derivatives based on a customer's order by withdrawing a certain amount of money and/or securities as a margin to guarantee the transaction. In performing its functions as an intermediary party for customers who transact in the futures exchange, the futures broker has an individual legal subject, namely Futures Broker Representative. This normative legal research with an approach to statutory and conceptual issues discusses the legal relations of futures broker representatives and their responsibilities in commodity futures trading which will be analyzed prescriptively with deductive reasoning. The result shows the legal relation between futures broker, futures broker representative and costumer that creates rights and obligations is a result of an alliance in the form of mandate and authorization in futures trading contracts. Violations committed by Futures Broker Representatives against the regulations made by the regulator will result in the imposition of sanctions both administratively and criminally. The futures Broker is responsible if there is an error made by the Futures Broker Representative. Then if there are customers who feel aggrieved, they can apply for compensation due to breach of contract of futures brokers.